Determining the hull shape changes of local deep-sea fishing boats according to geographical area in Peninsular Malaysia - 270074 Chua, Kwang Nguan (Sekudai : UTM, 1998)
Project Paper (Bachelor of Mechanical Engineering) - Universiti Teknologi Malaysia, 1998